Surface passivation investigation on ultra-thin atomic layer deposited aluminum oxide layers for their potential application to form tunnel layer passivated contacts. (6th July 2017) - Xin, Zheng; Ling, Zhi Peng; Nandakumar, Naomi; Kaur, Gurleen; Ke, Cangming; Liao, Baochen; Aberle, Armin G.; Stangl, Rolf
Abstract: The surface passivation performance of atomic layer deposited ultra-thin aluminium oxide layers with different thickness in the tunnel layer regime, i.e., ranging from one atomic cycle (∼0.13 nm) to 11 atomic cycles (∼1.5 nm) on n-type silicon wafers is studied. The effect of thickness and thermal activation on passivation performance is investigated with corona-voltage metrology to measure the interface defect density D it ( E ) and the total interface charge Q tot . Furthermore, the bonding configuration variation of the AlO x films under various post-deposition thermal activation conditions is analyzed by Fourier transform infrared spectroscopy. Additionally, poly(3, 4-ethylenedioxythiophene) poly(styrene sulfonate) is used as capping layer on ultra-thin AlO x tunneling layers to further reduce the surface recombination current density to values as low as 42 fA/cm 2 . This work is a useful reference for using ultra-thin ALD AlO x layers as tunnel layers in order to form hole selective passivated contacts for silicon solar cells.